Apparent treatment resistant hypertension and the risk of recurrent cardiovascular events and mortality in patients with established vascular disease. (1st July 2021) - Groenland, Eline H.; Bots, Michiel L.; Asselbergs, Folkert W.; de Borst, Gert J.; Kappelle, L. Jaap; Visseren, Frank L.J.; Spiering, Wilko; ,
Abstract: Aim: To quantify the relation between apparent treatment resistant hypertension (aTRH) and the risk of recurrent major adverse cardiovascular events (MACE including stroke, myocardial infarction and vascular death) and mortality in patients with stable vascular disease. Methods: 7455 hypertensive patients with symptomatic vascular disease were included from the ongoing UCC-SMART cohort between 1996 and 2019. aTRH was defined as an office blood pressure ≥140/90 mmHg despite treatment with ≥3 antihypertensive drugs including a diuretic. Cox proportional hazard models were used to quantify the relation between aTRH and the risk of recurrent MACE and all-cause mortality. In addition, survival for patients with aTRH was assessed, taking competing risk of non-vascular mortality into account. Results: A total of 1557 MACE and 1882 deaths occurred during a median follow-up of 9.0 years (interquartile range 4.8–13.1 years). Compared to patients with non-aTRH, the 614 patients (8%) with aTRH were at increased risk of cardiovascular mortality (HR 1.27; 95% CI 1.03–1.56) and death from any cause (HR 1.25; 95% CI 1.07–1.45) but not recurrent MACE (HR 1.13; 95% CI 0.95–1.34). At the age of 50 years, patients with aTRH after a first cardiovascular event on average had a 6.4 year shorter median life expectancy free of recurrent MACE than patients with non-aTRH. Conclusion: In hypertensive patients with clinically manifest vascular disease, aTRH is related to a higher risk of vascular death and death from any cause. Moreover, patients with aTRH after a first cardiovascular event have a 6.4 year shorter median life expectancy free of recurrent cardiovascular disease. Highlights: In hypertensive patients with vascular disease, aTRH is associated with a higher risk of (vascular) death Moreover, aTRH in these patients resulted in a substantial reduction in median life expectancy (free of recurrent MACE) These findings support the need for greater efforts to improve BP control in patients with aTRH and vascular disease